2004
DOI: 10.1113/jphysiol.2004.062349
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpolarized shifts in the voltage dependence of fast inactivation of Nav1.4 and Nav1.5 in a rat model of critical illness myopathy

Abstract: Critical illness myopathy is a disorder in which skeletal muscle becomes electrically inexcitable. We previously demonstrated that a shift in the voltage dependence of fast inactivation of sodium currents contributes to inexcitability of affected fibres in an animal model of critical illness myopathy in which denervated rat skeletal muscle is treated with corticosteroids (steroid-denervated; SD). In the current study we examined whether expression of Na v 1.5 contributes to the altered voltage dependence of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 37 publications
2
43
1
3
Order By: Relevance
“…Both reduced channel number and increased fast inactivation of channels occur in muscle in CIM (29,30,34). If reduction in channel number is the cause of reduced excitability, relief of sodium channel inactivation should not greatly increase action potential amplitude.…”
Section: Increased Inactivation Of Sodium Channels Contributes To Thementioning
confidence: 99%
See 1 more Smart Citation
“…Both reduced channel number and increased fast inactivation of channels occur in muscle in CIM (29,30,34). If reduction in channel number is the cause of reduced excitability, relief of sodium channel inactivation should not greatly increase action potential amplitude.…”
Section: Increased Inactivation Of Sodium Channels Contributes To Thementioning
confidence: 99%
“…In the CIM studies, we used voltage clamp techniques to directly study sodium currents in isolated muscle fibers and found that reduced numbers of channels did not fully account for the differences in excitability between severely affected and mildly affected muscle fibers (29). Instead, a hyperpolarized shift in the voltage dependence of sodium channel inactivation was the principal cause of reduced excitability (29,30,34). The hyperpolarized shift increased inactivation of sodium channels and reduced the number of channels available to open during action potentials.…”
Section: Figurementioning
confidence: 99%
“…Thus upregulation of Nav1.5 sodium channels could explain the presence of more inactivated sodium channels and hence reduced action potential generation, inexcitability and the clinical manifestation of weakness. However, although Nav1.5 sodium channels were present in SD muscle, they do not account for the alteration in sodium channel regulation [43,60]. This finding demonstrated that the primary cause of the loss of excitability of SD fibers is an alteration in the regulation of Nav1.4 sodium channels instead of the new expression of Nav1.5 channels.…”
Section: Inexcitability Of Sd Muscle Is Due To Abnormal Regulation Ofmentioning
confidence: 92%
“…A similar shift can be observed in our data (Table 2), consistent with an increased Na v 1.5 channel fraction in cardiac-conditioned versus control cells and the highest Na v 1.5 channel fraction in TTX-treated conditioned cells. Moreover, a mixed population of Na v 1.4 and Na v 1.5 channels should also reduce the slope of the voltage dependence of inactivation (8). Indeed, this was the case for both fast and slow inactivation in cardiacconditioned compared with control cells (compare K values in Table 2).…”
Section: Differentiation Of Control and Cardiac-conditioned Cellsmentioning
confidence: 99%